Analysis of Students' Understanding in Chemistry Learning with the Theme of Climate Change - Katarina Herwanti; Saptono Nugrohadi; Mega Novita; Stanislaus Christo Petra Nugraha (Proceeding International Conference on Digital Education and Social Science, 2024)
This study aims to evaluate students' understanding of climate change material in Chemistry learning at SMA Negeri 1 Salatiga. By analyzing data from 186 students who answered five HOTS-based questions after reading texts related to the impact of climate change and urbanization in Salatiga, this study found that the average student comprehension score reached 10.51 out of 13 maximum points. Student participation was relatively low with an engagement rate of only 43.2%. These findings provide insight into the effectiveness of environmental and climate change-based Chemistry learning strategies and recommend innovations to increase student engagement.